DIVERGENT REGULATION OF SIRT1 MEDIATES THE ENDOCRINE RESPONSE TO CALORIE RESTRICTION. (11th November 2018) - Bonkowski, M; Shawn, D; Lu, Y; Schultz, M; Reyes, J; Guarente, L; Sinclair, D
Abstract: Suppressed neuroendocrine signaling is a common trait in many long-lived mouse mutants and mice on calorie restriction. Loss-of-function mutations in the pituitary Pit1 and Prop1 genes in Snell and Ames dwarf mice were the first mutations known to extend lifespan in mammals. Evidence indicates that SIRT1 plays a major role in mediating the effects of calorie restriction (CR) on behavior, metabolism, and longevity. In most peripheral tissues, CR leads to an increase in SIRT1 protein abundance. In the pituitary however, we find that SIRT1 is down-regulated during CR, coincident with reduced pituitary size, testis weight, sperm count, circulating levels of pituitary hormones, and longer lifespan. We hypothesize that reduced expression of pituitary SIRT1 may mediate the suppression of neuroendocrine hormones normally observed in mice on CR. To test this, we generated pituitary-specific SIRT1 knockout (PitSKO) mice. Consistent with this hypothesis, PitSKO mice are dwarfed, with CR-like reductions in fertility and circulating pituitary hormones and reductions in PIT1-regulated transcripts compared to control mice. Our evidence indicates that SIRT1 is a PIT1 coactivator that binds to and deacetylates specific lysine residues on PIT1 altering its transcriptional activity. PitSKO mice are long-lived compared to WT controls, providing the first demonstration of a SIRT1 knockout mouse with extended longevity. These data suggest that SIRT1 drives growth and reproduction when food is in excess and that pituitary SIRT1-PIT1 regulation mediates the the effects of CR on suppressed neuroendocrine signaling from the pituitary.